La partecipazione politica nel tempo della post-democrazia - Michele Sorice (Culture e Studi del Sociale)
The concept of participation has been defined in different ways over time and also the practices of political participation have been interpreted and classified in many different ways in the political procedures of the representative democracies. Similarly, the notion of conflict presents various critical points: even in some forms of democratic innovation, the conflict has been expunged or anesthetized. The growing centrality of the digital ecosystem represents a new variable: on the one hand, in fact, it offers spaces for mobilization and political action, on the other hand, it reveals itself as the outcome of a digital capitalism in which the dealignment of power between citizens and platforms is resolved clearly in favour of the latter. The emergence of what has been defined as “platform society” is connected with the affirmation of post-democracy. The public sphere - increasingly fragmented - is also evolving towards what has been defined as the “post-public sphere”. The transformations taking place can be better understood if framed in the “paradigm of the crisis”, made even more evident in the time of the pandemic. A review of many concepts then becomes necessary, within a scientific horizon that does not renounce to critically analyse its own tools.